Correction: Quantum error correction with molecular spin qudits. Issue 34 (29th July 2022) - Chizzini, Mario; Crippa, Luca; Zaccardi, Luca; Macaluso, Emilio; Carretta, Stefano; Chiesa, Alessandro; Santini, Paolo
Abstract : Correction for 'Quantum error correction with molecular spin qudits' by Mario Chizzini et al., Phys. Chem. Chem. Phys., 2022, ; https://doi.org/10.1039/D2CP01228F .